MO468NEW URINARY BIOMARKERS DETECT SUBCLINICAL RENAL DAMAGE AFTER SEVERAL ACUTE KIDNEY INJURY EPISODES. (29th May 2021) - Massaro, Giampiero A; Mercado-Hernandez, Joana; Carbajo-Uña, Ana; Fuentes-Calvo, Isabel; Sancho Martinez, Sandra M; Ramudo, Laura; Lopez-Hernandez, Francisco J; Martinez Salgado, Carlos
Abstract: Background and Aims: Acute kidney injury (AKI) represents a clinical problem due to its increasing prevalence and association with further morbidities. Observational studies have shown that AKI increases the risk of a new AKI episode, chronic kidney disease (CKD), CKD progression, end-stage renal disease (ESRD), and mortality. Serum creatinine (sCr) is the parameter most used by clinicians for determining AKI and the subsequent recovery, however its use presents several limitations. sCr lacks sensitivity for AKI and provides minimal insight into the renal structure. Indeed, increases in sCr are observed only when glomerular filtration rate decreases more than 50%. Therefore, new markers need to be identified to predict recovery after AKI and to detect residual structural alterations that can cause progression to CKD. We hypothesised that after AKI, there are renal structural abnormalities that cannot be detected by common clinical parameters but may be detected by urinary biomarkers. Method: We used 4 weeks old male Wistar rats. Animals were divided into 5 experimental groups: Control group: SHAM operated rats, saline solution i.p.; "CDDP5-SHAM" group: 5 mg/kg cisplatin i.p.; "Ctrl-I/R60" group: 60-minute renal ischemia reperfusion in the left kidney; "CDDP5-I/R60" group: 5 mg/kg cisplatin i.p. and after renal function normalization, 60-minute ischemia-reperfusion (I/R60); "5/6 NEF" group: 5/6 nephrectomy. Blood and urine were collected at: day 0 (basal); day 4 (AKI development); day 8 (normalized renal function after AKI and induction of renal ischemia); day 9 (1 day after ischemia); day 13, day 20 and every week thereafter. Renal function was analyzed by sCr, creatinine clearance, blood urea nitrogen and proteinuria determination using colorimetric methods. Urinary biomarkers were analyzed at day 20 (12 days after the second damage and 20 after the first one) by western blot and ELISA. Animals were sacrificed at the same time point in which urinary biomarkers were determined, and renal tissue samples were stained with Masson´s trichrome, Sirius Red and Periodic Acid-Schiff for histological analysis. Results: Frequency of AKI episodes is related to the amount and degree of subclinical alterations detected in the kidneys, even though renal filtration is apparently normal. We characterized a novel panel of urinary biomarkers (bk1-bk4) several days after the last insult (day 20) when renal function appeared normal; these biomarkers were present in highest concentrations in the CDDP5-I/R60 experimental group. Conclusion: These results demonstrate the importance of the clinical implementation of biomarkers as useful tools for medical support and underline the limitations of the clinical parameters (e.g. sCr, estimated GFR) currently used for renal function assessment. The frequency of AKI episodes is related to a poor prognosis, so a follow up is necessary after AKI episodes in order to prevent mortality and progression of the disease.